PENINGKATAN PRODUKTIVITAS KERJA GURU MELALUI BIMBINGAN INDIVIDUAL DI SDN 05 LEMBAH MELINTANG TAHUN PELAJARAN 2018/2019 - Elida, Elida (Ensiklopedia Education Review, 2019)
The purpose of this research is to find out: (1) The steps of implementing individual guidance by the principal to teachers to improve teacher work productivity at SDN 05 Lembah Melintang, (2) The magnitude of increasing teacher work productivity after the implementation of individual guidance was developed by headmaster. This research is a school action research that is analyzed with a qualitative approach. The study was conducted at SDN 05 Lembah Melintang in the first semester of the 2018/2019 school year. The results obtained are: (1) The implementation of individual guidance can be developed by basing the steps of: (1) Guidance of developing learning models through comparative studies and follow-up planning, followed by SWOT analysis guidance; (2) Guidance on the administration of education administration, followed by the provision of direct feed beack on the work of teachers; (3) Advanced guidance sets reliable targets, developed with joint evaluation of other teacher program targets that are also experiencing the same problem; (4) Guidance on how to carry out collaboration with other teachers in a deeper way, to the ability to show the materials needed by other teachers; (5) Guidance for effective and efficient work strategies, which are developed by training to determine optimal kauntitas numbers and how to measure them through scoring techniques; (6) Developing motivational guidance; (7) Building independence so that teachers avoid plagiarism-based activities, and guidance for effective planning; (8) Guidance for making effective work planning coupled with innovative aspects; (9) Encouraging teachers to implement teacher competency improvement programs through seminars and workshops followed by the implementation of new experiences from teacher activities; (2) The implementation of individual guidance is able to increase the work productivity of teachers in schools because of the completion of teacher problems in the development and implementation of learning programs in schools.